MOTIVASI SULUK 5 HARI DAN KETEKUNAN BERIBADAH PENGAMAL TAREKAT NAQSYABANDIYAH SYEKH H. MHD.IHSAN HARAHAP (Studi Analisis pada Murid Usia Minus 40 Tahun) - ARMYN HASIBUAN (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
This research is a study of analysis on a pupil's age minus 40 years. The formulation of the problem is what motivation suluk 5 days on the Shaykh Naqshbandi guidance h. Mhd. Ihsan Harahap and how perseverance serve pupils aged 40 years after it was completed minus suluk 5 days.This research is descriptive qualitative research. The time this research was planned for 6 months where the subject is referred to in this research was Sheikh h. Mhd. Ihsan Harahap and his disciple. The method used in determining the subject of the research using the method of pourposive sampling.The results of the study found the description about the motivation of suluk 5 days on the Shaykh Naqshbandi guidance H. Mhd. Ihsan Harahap viewable from two things; first the willingness of his congregation and the second from the whims of Sheikh h. Mhd. Ihsan Harahap and Caliphs as the loyal right hand man helped him. Motivation in the presence the call of soul worship in the disciples. Then extrinsic existence of socialization through Da'wah of Shaykh, the influence of friends, the mindset of people that worship time efficiency in suluk